A Generalized Index of Diversification: Trends in U.S. Manufacturing - Gollop, Frank M.; Monahan, James L. (The Review of Economics and Statistics, 1991)
An index of diversification suitable for manufacturing plants and firms is defined as a function of product number, distribution, and dissimilarity. A novel feature of the index is its continuous treatment of product heterogeneity. Using "Census of Manufactures" data files, the index is constructed for each establishment and each enterprise surveyed in the 1963-1982 censuses. Results are reported at the 2-digit SIC level. While quantifying the upward trend in enterprise diversification, the index reveals an ubiquitous and persistent decline in establishment diversification. Over time, enterprises are shifting toward a more diverse portfolio of increasingly homogeneous plants. Technical economies of scope appear to play little role in explaining the measured increase in enterprise diversification. Copyright 1991 by MIT Press.